2005
DOI: 10.1007/s00222-004-0420-1
|View full text |Cite
|
Sign up to set email alerts
|

Hermite polynomials and helicoidal minimal surfaces

Abstract: The main objective of this paper is to construct smooth 1-parameter families of embedded minimal surfaces in euclidean space that are invariant under a screw motion and are asymptotic to the helicoid. Some of these families are significant because they generalize the screw motion invariant helicoid with handles and thus suggest a pathway to the construction of higher genus helicoids. As a byproduct, we are able to relate limits of minimal surface families to the zero-sets of Hermite polynomials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 7 publications
5
34
0
Order By: Relevance
“…As said before, the method also works for surfaces of infinite total curvature. For instance, Traizet and Weber [201] have used these ideas to perturb weak limits of planes and helicoids, thereby producing the first non-classical examples of minimal parking garage surfaces (see the comments after Theorems 4.5 and 4.7; also see the survey [116] for a more detailed explanation of this concept). Very recently, Traizet [200] has applied this method to produce a properly embedded minimal surface in R 3 with infinite genus and one limit end; see Footnote 43 for the importance of this new example.…”
Section: Theorem 31 (Schoen [188]) the Catenoid Is The Unique Complmentioning
confidence: 99%
“…As said before, the method also works for surfaces of infinite total curvature. For instance, Traizet and Weber [201] have used these ideas to perturb weak limits of planes and helicoids, thereby producing the first non-classical examples of minimal parking garage surfaces (see the comments after Theorems 4.5 and 4.7; also see the survey [116] for a more detailed explanation of this concept). Very recently, Traizet [200] has applied this method to produce a properly embedded minimal surface in R 3 with infinite genus and one limit end; see Footnote 43 for the importance of this new example.…”
Section: Theorem 31 (Schoen [188]) the Catenoid Is The Unique Complmentioning
confidence: 99%
“…They also prove that if M ∈ M has finite positive genus and just one end, then it is asymptotic to the end of the helicoid and can be defined analytically in terms of meromorphic data on its conformal completion, which is a closed Riemann surface. This theoretical result together with the recent theorems developed by Weber and Traizet [39] and by Hoffman, Weber and Wolf [19] provide a theory on which a proof of Conjecture 2 might be based.…”
Section: Conjecture 3 (Infinite Topology Conjecture (Meeks)) a Noncommentioning
confidence: 74%
“…We refer the reader to section 11 of [26] where the basic theory of parking garage structures is developed, classical examples are given. We also refer the reader to [39] where it is shown that certain limiting minimal parking garage structures can be analytically untwisted via the implicit function theorem to produce one-parameter families of interesting periodic minimal surfaces that converge to it. …”
Section: And We Letmentioning
confidence: 99%
“…Meeks and Rosenberg [38] have proposed the following question (which they proved for k = 0). There is a large number of examples constructed by desingularization, see for instance Kapouleas [21] and Traizet [61] for the non-periodic case and Traizet and Weber [62,64] for the periodic one.…”
Section: Minimal Surfaces With Finite Topology In Rmentioning
confidence: 99%